Peran Organisasi Ekstrakurikuler dalam Pembentukan Karakter Siswa - Maulani, Novia; Pagestu, Jesti Argi Yuan; Erika, Cintami Nur; Nuphanudin, Nuphanudin; Windasari, Windasari (JURNAL MANAJEMEN PENDIDIKAN, 2024)
THE ROLE OF EXTRACURRICULAR ORGANIZATIONS IN BUILDING STUDENT CHARACTER AT SMAN 1 DRIYOREJO Extracurricular activities are activities carried out outside learning hours, intracurricular activities and co-curricular activities under the guidance and supervision of educational units. This study aims to find out (1) The extracurricular organizations at SMAN 1 Driyorejo (2) the role of extracurricular organizations in building character at SMA Negeri 1 Driyorejo. This research uses a qualitative approach method using observation, interviews and documentation studies as data collection techniques and focuses on several organizations in SMA Negeri 1 Driyorejo. Based on research conducted by observation and interviews with students of SMAN 1 Driyorejo, several interesting things were found. The results showed that (1) There were 23 extracurriculars held at SMAN 1 Driyorejo consisting of academic and non-academic fields, including PMR, PASKIBRAKA, futsal, basketball, Scouting, Pencak silat, science and others. (2) The role of extracurricular activities in character building, namely providing opportunities for students to develop students' skills and interests. So that it can help students develop positive values such as discipline, diligent and diligent, responsibility, have a leadership spirit, social care, care for the environment, commitment, have a high spirit and earnest.